2008
DOI: 10.1002/glia.20650
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes, but not olfactory ensheathing cells or Schwann cells, promote myelination of CNS axons in vitro

Abstract: We have examined the interaction between olfactory ensheathing cells (OECs), Schwann cells (SC), oligodendrocytes, and CNS axons using cultures generated from embryonic rat spinal cord. Oligodendrocyte process extension and myelination in these cultures was poor if the cells were plated on OECs or SCs. Myelin internodes and nodes of Ranvier formed frequently if these cultures were plated onto monolayers of neurosphere-derived astrocytes (NsAs). In the myelinated fibers generated on NsAs, Nav channels, caspr, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(133 citation statements)
references
References 67 publications
3
130
0
Order By: Relevance
“…In our models, oligodendrocytes are always colocalized with astrocytes, which may suggest their interdependence in terms of survival, migration, and/or differentiation. This latter observation is in agreement with a recent study highlighting the role of astrocytes in the promotion of myelination in the CNS (Sorensen et al, 2008). In our study, ectopic oligodendrocytes and astrocytes were never observed in more distal parts of peripheral nerves, although the DRGs were also colonized (data not shown).…”
Section: Control Of Cns/pns Boundarysupporting
confidence: 94%
“…In our models, oligodendrocytes are always colocalized with astrocytes, which may suggest their interdependence in terms of survival, migration, and/or differentiation. This latter observation is in agreement with a recent study highlighting the role of astrocytes in the promotion of myelination in the CNS (Sorensen et al, 2008). In our study, ectopic oligodendrocytes and astrocytes were never observed in more distal parts of peripheral nerves, although the DRGs were also colonized (data not shown).…”
Section: Control Of Cns/pns Boundarysupporting
confidence: 94%
“…Astrocytes or forebrain mixed cells were isolated from cerebral hemispheres of E18 mice and cultured following previously described methods with minor modifications 27, 28, 29, 30, 31. Cultures were kept in a humidified incubator at 37°C and 7.5% CO 2 at all times.…”
Section: Methodsmentioning
confidence: 99%
“…Myelinating CNS cultures were set up as previously outlined, 24,25 with a couple of minor modifications. They comprise a monolayer of astrocytes on top of which are plated mixed rat spinal cord cells.…”
Section: Cell Seedingmentioning
confidence: 99%
“…Astrocytes are essential for cell survival and myelination. 24 Briefly, striatum were collected from P1 Sprague-Dawley rats in Liebowitz (L15; Invitrogen) media and dissociated mechanically before suspension in neurosphere media (Dulbecco's modified Eagle's medium, DMEM/F12 (1:1), 0.6% glucose, 2 mM glutamine (Invitrogen), insulin (25 mg/mL; Sigma), 5 mM Hepes (Sigma), 0.105% NaHCO 3 (Sigma), 5000 IU/mL penicillin (Invitrogen), 5 mg/mL streptomycin (Invitrogen), 100 mg/mL apotransferrin, 20 nM progesterone, 60 mM putrescine, and 30 nM sodium selenite (all Sigma) supplemented with 20 ng/mL mouse submaxillary gland epidermal growth factor (EGF; R&D systems) and cultured as neurospheres for 7-10 days at 37°C, 7% CO 2, with supplementation of the media every alternate day.…”
Section: Cell Seedingmentioning
confidence: 99%
See 1 more Smart Citation